A gradual increase of iron toward the medial‐inferior tip of the subthalamic nucleus. Issue 9 (4th March 2014) - de Hollander, Gilles; Keuken, Max C.; Bazin, Pierre‐Louis; Weiss, Marcel; Neumann, Jane; Reimann, Katja; Wähnert, Miriam; Turner, Robert; Forstmann, Birte U.; Schäfer, Andreas
Abstract The subthalamic nucleus (STN) is an important node of the cortico‐basal ganglia network and the main target of deep brain stimulation (DBS) in Parkinson's disease. Histological studies have revealed an inhomogeneous iron distribution within the STN, which has been related to putative subdivisions within this nucleus. Here, we investigate the iron distribution in more detail using quantitative susceptibility mapping (QSM), a novel magnetic resonance imaging (MRI) contrast mechanism. QSM allows for detailed assessment of iron content in both in vivo and postmortem tissue. Twelve human participants and 7 postmortem brain samples containing the STN were scanned using ultra‐high field 7 Tesla (T) MRI. Iron concentrations were found to be higher in the medial‐inferior tip of the STN. Using quantitative methods we show that the increase of iron concentration towards the medial‐inferior tip is of a gradual rather than a discrete nature. Hum Brain Mapp 35:4440–4449, 2014. © 2014 Wiley Periodicals, Inc.